Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) di PT Erindo Mandiri Prigen - Lailatul Firdausi; Khotim Fadhli (FEB Universitas Maritim Semarang, 2024)
Organizational Citizenship Behavior (OCB) refers to voluntary actions that are not directly rewarded by the formal reward system but that contribute to organizational effectiveness. Organizational citizenship behavior (OCB) is a reflection of the added value of employees and contributes to job performance, job satisfaction, and organizational commitment. PT Erindo Mandiri is a company engaged in the production of bottled mineral water. This study aims to evaluate the effect of job satisfaction and organizational commitment on organizational citizenship behavior (OCB) at PT Erindo Mandiri, as well as to ascertain how HR management can improve company effectiveness through OCB. In this case, the researcher employs an associative method with the objective of discerning the impact of job satisfaction (X1) and organizational commitment (X2) on the organizational citizenship behavior variable (Y) at PT Erindo Madiri. The results of the research conducted at PT Erindo Mandiri indicate that job satisfaction and organizational commitment exert a positive influence on organizational citizenship behavior (OCB). The conjunction of these two variables engenders augmented individual and collective efficacy, as well as organizational systems that culminate in superior HR performance, characterized by minimal absenteeism and negligible deviations.